2021
DOI: 10.3389/fimmu.2021.789334
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacomicrobiology of Methotrexate in Rheumatoid Arthritis: Gut Microbiome as Predictor of Therapeutic Response

Abstract: Rheumatoid arthritis (RA) is a disabling autoimmune disease with invasive arthritis as the main manifestation and synovitis as the basic pathological change, which can cause progressive destruction of articular cartilage and bone, ultimately leading to joint deformity and loss of function. Since its introduction in the 1980s and its widespread use in the treatment of RA, low-dose methotrexate (MTX) therapy has dramatically changed the course and outcome of RA treatment. The clinical use of this drug will be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 144 publications
(202 reference statements)
0
12
0
1
Order By: Relevance
“…Methotrexate (MTX) was originally designed in the 1940s as a folate antagonist for treatment of various cancers [ 6 ]. In the management of early and established RA, MTX is recommended as a first-line drug by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR) [ 7 ]. However, it has no significant effect and is accompanied by different side effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate (MTX) was originally designed in the 1940s as a folate antagonist for treatment of various cancers [ 6 ]. In the management of early and established RA, MTX is recommended as a first-line drug by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR) [ 7 ]. However, it has no significant effect and is accompanied by different side effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…DMARDs may indirectly affect and remodel the structure and function of gut microbiota to regulate systemic immunity. Studies have demonstrated that microbial differences in the gastrointestinal tract of RA patients may partially determine the bioavailability and subsequent clinical outcome of methotrexate ( 63 , 64 ). In turn, methotrexate treatment was shown to partially restore normal gut microbiota composition in RA patients ( 16 , 65 ).…”
Section: Therapeutic Modulation Of the Gut Microbiota And Impact Of G...mentioning
confidence: 99%
“…Methotrexate may also influence the community of intestinal microorganisms, regulating their diversity and function. It inhibits the growth of intestinal bacterial strains in a dose-dependent manner, which results in reduced stimulation of immune system activation and decreased tolerance to Treg cell induction [ 101 ]. In addition, the use of hydroxychloroquine in SLE appears to reduce the abundance of Enterobacteriaceae [ 102 ].…”
Section: Potential Strategies Of Gut Microbiota Modulationmentioning
confidence: 99%